EVALUASI PENGARUH PENGGUNAAN BAHAN PELEDAK TERHADAP BATUAN HASIL PELEDAKAN OVERBURDEN PIT 2 BANKO BARAT PT BUKIT ASAM Tbk - Orin Arneta; Ridho Yovanda; Dedi Yansen (Jurnal Humaniora & Sosial Sains, 2025)
This study aims to conduct a comprehensive evaluation of the key components and effectiveness of blasting activities in the PT Bukit Asam mining area, specifically in Pit 2 Banko Barat. The main objective is to quantitatively determine the distribution of blasted rock fragmentation, as this is a critical factor that affects the productivity of the entire mining operation cycle, from ease of digging to crusher efficiency. To achieve this objective, this study applies a systematic methodology, beginning with field observations to directly observe each stage of the blasting process, from blasthole preparation to post-blast testing. Primary data collection includes blasting geometry parameters (burden and spacing), the types of explosives used such as ANFO and Powergel, and visual documentation of the pile of blasted material (muckpile). This data is complemented by secondary data in the form of geological conditions of the area. The culmination of the analysis was carried out using Split Desktop software, which analyzes digital images of the muckpile to generate fragmentation distribution curves. The results show that the pattern and explosives used have been adjusted to field conditions, where their effectiveness is validated through measured fragmentation data that serves as the basis for further blasting optimization.